Rancang Bangun Sistem Pendataan Hardware - Alvin Anzas Islami; Siti Ramadhani (Prodi Sistem Informasi Universitas Dharma Andalas, 2021)
Currently, advances in information technology have had a tremendous impact in all aspects of life, especially PTIPD UIN SUSKA RIAU also requires information technology that can assist employees' work. With information technology, data at PTIPD UIN SUSKA RIAU can be processed quickly and efficiently to increase the effectiveness and efficiency of completing work and the scope of communication and information. The processing of hardware data collection documentation carried out by PTIPD is still carried out outside the system, causing the data collection documentation process to be longer and less efficient. The solution given to overcome this problem is to make a hardware data collection system. Making a hardware data collection system included in the system provides information about the list of goods and officers. While the software used is a DBMS (DataBase Management System) used as a data storage medium is MySql, the programming languages ​​PHP, CSS, JavaScript, and HTML are used as interfaces, which aim to make it easier users and administrators to manipulate data.